2021
DOI: 10.1186/s10020-021-00360-w
|View full text |Cite
|
Sign up to set email alerts
|

G protein coupled estrogen receptor attenuates mechanical stress-mediated apoptosis of chondrocyte in osteoarthritis via suppression of Piezo1

Abstract: Background Apoptosis of chondrocyte is involved in osteoarthritis (OA) pathogenesis, and mechanical stress plays a key role in this process by activation of Piezo1. However, the negative regulation of signal conduction mediated by mechanical stress is still unclear. Here, we elucidate that the critical role of G protein coupled estrogen receptor (GPER) in the regulation of mechanical stress-mediated signal transduction and chondrocyte apoptosis. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 42 publications
0
31
0
Order By: Relevance
“…Moreover, molecular docking showed that Bai has high binding affinity for the top targets (BAX, BCL2, and Caspase 3). Accumulating studies have revealed that articular chondrocyte apoptosis occurs under the action of endogenous or exogenous stimulation in patients with OA ( Qiu et al, 2021 ; Sun et al, 2021 ). Chondrocyte apoptosis is one of the important reasons for injury to and loss of articular cartilage and an important mechanism for the occurrence and development of OA ( Wang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, molecular docking showed that Bai has high binding affinity for the top targets (BAX, BCL2, and Caspase 3). Accumulating studies have revealed that articular chondrocyte apoptosis occurs under the action of endogenous or exogenous stimulation in patients with OA ( Qiu et al, 2021 ; Sun et al, 2021 ). Chondrocyte apoptosis is one of the important reasons for injury to and loss of articular cartilage and an important mechanism for the occurrence and development of OA ( Wang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Piezo1 inhibition reduces mechanical shock-induced activation of NLRP3 inflammasome and IL-1β expression in nucleus pulposus cells ( 95 ). In addition, G protein-coupled estrogen receptor attenuates mechanical stress-mediated apoptosis of chondrocytes in osteoarthritis via suppression of Piezo1 ( 96 ). Mechanical stretching of the lumbar spine upregulates Piezo1, NLRP3, ASC and IL-1β in nucleus pulposus cells.…”
Section: Piezo1 Channel-mediated Chronic Inflammationmentioning
confidence: 99%
“…The range of cytoskeletal variation can be modulated by GPER, which is thought to be involved in mechanical transduction [69,70]. When mechanical stress-mediated chondrocyte apoptosis occurs, chondrocyte apoptosis in osteoarthritis can be attenuated by GPER via causing the inhibition of Piezo 1 protein [71].…”
Section: Gper Roles In Stressmentioning
confidence: 99%